Performativeness and gender: gender settings in school days - Chotolli, Wesley Piante [UNESP]; Brancaleoni, Ana Paula Leivar [UNESP] (Univ Fed Rio De Janeiro, Fac Letras, 2022)
Considering the school space an important mechanism of socialization, it is observed how young people experience their experiences in this context, constituting the identities around socially consecrated practices. The objective is to understand how the school experience is marked by issues gendered around binarisms. The queer theories were used as theoretical support, producing an ethnographic qualitative analysis in the case study format of a third grade high school classroom. Semi-structured interviews were conducted, analyzing how the students perceived the relationship between identity and gender. It is possible to conclude that the students classify the practices associating them with the image of masculinity or femininity, allowing the understanding of the actions in the school days.
Keywords: High School; Gender; Identity